2019
DOI: 10.1093/jcr/ucz006
|View full text |Cite
|
Sign up to set email alerts
|

How Well Do Consumer-Brand Relationships Drive Customer Brand Loyalty? Generalizations from a Meta-Analysis of Brand Relationship Elasticities

Abstract: To advance understanding of how well different types of brand relationships drive customer brand loyalty and to help companies improve the effectiveness of their relationship-building investments, this article conducts a meta-analysis of the link between five consumer-brand relationship constructs and customer brand loyalty. The analysis of 588 elasticities from 290 studies reported in 255 publications over 24 years (n = 348,541 across 46 countries) reveals that the aggregate brand relationship elasticity is .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
159
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(165 citation statements)
references
References 195 publications
(222 reference statements)
3
159
0
3
Order By: Relevance
“…Our major findings were that (1) brand love is typically less passionate and intense than interpersonal love (especially romantic love) (Ahuvia, 2005b ; Albert et al, 2013 ; Langner et al, 2015 ; Bagozzi et al, 2016 ); (2) altruistic elements were not observed in brand love, although these are crucial elements in interpersonal love (Batra et al, 2012 ; Albert et al, 2013 ; Langner et al, 2015 ); (3) the core of brand love involves incorporating the loved object into the self (Ahuvia, 1992 , 1993 , 2005a , b ; Escalas and Bettman, 2003 , 2015 ; Thomson et al, 2005 ; Park et al, 2006 , 2008 , 2009 ; Ahuvia et al, 2008 ; Albert et al, 2008 , 2009 , 2013 ; Reiman and Aron, 2009 ; Lastovicka and Sirianni, 2011 ; Batra et al, 2012 ; Albert and Merunka, 2013 ; Bagozzi et al, 2016 ; Khamitov et al, 2019 ). Our findings support those of previous studies on brand love.…”
Section: Conclusion: What Is Brand Love?mentioning
confidence: 99%
See 2 more Smart Citations
“…Our major findings were that (1) brand love is typically less passionate and intense than interpersonal love (especially romantic love) (Ahuvia, 2005b ; Albert et al, 2013 ; Langner et al, 2015 ; Bagozzi et al, 2016 ); (2) altruistic elements were not observed in brand love, although these are crucial elements in interpersonal love (Batra et al, 2012 ; Albert et al, 2013 ; Langner et al, 2015 ); (3) the core of brand love involves incorporating the loved object into the self (Ahuvia, 1992 , 1993 , 2005a , b ; Escalas and Bettman, 2003 , 2015 ; Thomson et al, 2005 ; Park et al, 2006 , 2008 , 2009 ; Ahuvia et al, 2008 ; Albert et al, 2008 , 2009 , 2013 ; Reiman and Aron, 2009 ; Lastovicka and Sirianni, 2011 ; Batra et al, 2012 ; Albert and Merunka, 2013 ; Bagozzi et al, 2016 ; Khamitov et al, 2019 ). Our findings support those of previous studies on brand love.…”
Section: Conclusion: What Is Brand Love?mentioning
confidence: 99%
“…This relationship has been defined as brand love, brand attachment, and/or brand commitment (Fournier, 1998;Ahluwalia et al, 2000;Thomson et al, 2005;Carroll and Ahuvia, 2006;Park et al, 2006Park et al, , 2009Batra et al, 2012). These emotional relationships between consumers and brands can contribute to loyalty, corporate growth, and long-term profitability (Thomson et al, 2005;Carroll and Ahuvia, 2006;Albert et al, 2008;Khamitov et al, 2019). Consumers with strong emotional bonds to their favorite brands attribute positive traits to them and exhibit strong intentions in protecting their beloved brand if it is maligned (Park et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tak heran, kajian budaya merek selama ini merujuk pada kode-kode budaya merek, seperti gambar-gambar, sejarah, mitos, seni, dan lainlain yang memengaruhi makna dan nilai merek di pasar. Hal ini berimplikasi pada pemahaman dan interpretasi budaya dalam dua ranah (Schroeder, 2009) (Kapferer, 2004). Kajian kultural yang ada juga hanya memahami merek sebagai obyek komunikatif yang memenuhi keinginan manajer merek untuk menjadikan konsumen membeli produknya, jadi semacam obyek simbolis dari identitas merek (Faurholt-Csaba & Bengtsson, 2006).…”
Section: Masyarakat Banyumas Keberatan Merekunclassified
“…However, there is no consensus in the scientific literature on the factors that shape customer loyalty. A certain group of authors [19,20,21,4,22,23] identify brand image, brand trust, brand affect and customer satisfaction as the most important factors contributing to increasing customer loyalty. According to Rauyruen and Miller, the most significant factors shaping customer loyalty include service quality, customer value, trust and commitment [24].…”
mentioning
confidence: 99%